Survival of invasive bladder cancer patients, 1998–2009; a central and northern Denmark population-based cohort study - Lund L; Erichsen R; Nørgaard M; Larsen EH; Borre M; Jacobsen J (Clinical Epidemiology, 2011)
Lars Lund1,2, R Erichsen1, M Nørgaard1, E H Larsen3, M Borre4, J Jacobsen11Department of Clinical Epidemiology, Aarhus University Hospital, Denmark; 2Department of Urology, Viborg Hospital, Denmark; 3Department of Urology, Aarhus University Hospital, Aalborg, Denmark; 4Department of Urology, Aarhus University Hospital, Skejby, DenmarkObjective: Invasive bladder cancer (IBC) is a common urological malignancy accounting for 4%–5% of all cancers in Denmark. Our aim was to examine possible changes in short- and long-term survival of patients with IBC during 1998–2009.Study design and setting: Data on all patients (N = 4032) with an incident diagnosis of IBC within a population of 1.8 million were retrieved from the Danish National Registry of Patients from 1998 to 2009. We computed survival after 1, 3, and 5 years, stratified by age and gender, and estimated mortality rate ratios (MRR) using Cox proportional hazard regression to compare mortality over time, controlling for age and gender. Data on tumor stage or histology were not included.Results: During the study period, the annual numbers of incident IBC patients remained stable. The median age was 74 years in each of the four 3-year periods in the study. The survival was relatively stable during the first three periods, whilst data from the last period showed modest improvement. The overall 1-year survival increased from 68% in 1998–2000 to 70% in 2007–2009, corresponding to an age and gender adjusted MRR of 0.89 (95% confidence interval [CI] 0.76–1.03). The 3- and 5-year survival was predicted to increase from 44% to 49% and from 35% to 40% respectively. This corresponded to a 3-year age and gender adjusted MRR of 0.87 (95% CI 0.77–0.98) and a 5-year MRR of 0.88 (95% CI 0.79–0.99). The 1-, 3-, and 5-year survival increased for men in all age groups (<70 years, 70–79 years, ≥80 years) and in women only in the 70–79-year age group. Conclusion: The survival of IBC patients increased slightly in northern and central Denmark in the 1998–2009 period.Keywords: outcome research, MRR, mortality rate ratio